2016
DOI: 10.4238/gmr15048886
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity, anti-proliferative activity, and amino acid profiles of ethanolic extracts of edible mushrooms

Abstract: ABSTRACT. Biological activities of various mushrooms have recently been discovered, particularly, immunomodulatory and antitumor activities. Herein, three edible mushrooms, Auricularia auricula-judae (AA), Pleurotus abalonus (PA) and Pleurotus sajor-caju (PS) extracted using Soxhlet ethanol extraction were evaluated for their antioxidative, anti-proliferative effects on leukemia cells. Using the Folin-Ciocalteau method and Trolox equivalent antioxidant capacity assay, phenolics and antioxidant activity were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…Similarly, LDH leakage demonstrated that PC exhibited cytotoxic effects on human blood cells at the mentioned doses. P. abalonus (500 µg /ml) and Auricularia auricula-judae (250-500 µg/ml) reduced cell viability [29]. Our results showed that the cytotoxic effect of hot water extract from mycelia of PC is in good agreement with mentioned studies.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, LDH leakage demonstrated that PC exhibited cytotoxic effects on human blood cells at the mentioned doses. P. abalonus (500 µg /ml) and Auricularia auricula-judae (250-500 µg/ml) reduced cell viability [29]. Our results showed that the cytotoxic effect of hot water extract from mycelia of PC is in good agreement with mentioned studies.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the extract did not reveal toxicity for non-tumour cells (primary PLP2), up to the maximal concentration tested (400 μg/ml). Some studies have also demonstrated that PSC methanolic extract had effects on U937 (Panthong, Boonsathorn, & Chuchawankul, 2016) and sarcoma 180 (Assis et al, 2013).…”
Section: Cytotoxicity In Tumour and Non-tumour Cellsmentioning
confidence: 99%
“…(31.56 ± 1.58 mg/g). Proline amino acid was observed in minimum amount among all extracts as discussed by (64) (65). Their occurrence in low concentration is might be due to their non-essential nature.…”
Section: Discussionmentioning
confidence: 83%